2001
DOI: 10.1002/cne.1384
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of protein phosphatases‐1α and ‐1γ1 and the D1 dopamine receptor in primate prefrontal cortex: Evidence for discrete populations of spines

Abstract: The function of G protein-coupled receptors depends on the availability of the appropriate signal transduction proteins in close proximity to the receptor. We have examined and quantified in primate prefrontal cortex the subcellular distribution of two isoforms of protein phosphatase-1 (PP1), PP1 alpha and PP1 gamma 1, which are components of the signal transduction pathway accessed by the D(1) dopamine receptor. Both PP1 alpha- and PP1 gamma 1-labeled puncta are seen in cortex, basal ganglia, hippocampus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…This finding is presumably a reflection of inappropriate biochemical context, and it highlights the need to identify possible phosphoprotein substrates regulated specifically by phactr͞PP1 holoenzyme complexes. PP1 is highly enriched in spine heads and in PSD fractions prepared from brain homogenate (6,22,23,(25)(26)(27). Phactr-1 colocalized with PP1 at synapses and thus may play a role in regulation of substrates controlling synaptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is presumably a reflection of inappropriate biochemical context, and it highlights the need to identify possible phosphoprotein substrates regulated specifically by phactr͞PP1 holoenzyme complexes. PP1 is highly enriched in spine heads and in PSD fractions prepared from brain homogenate (6,22,23,(25)(26)(27). Phactr-1 colocalized with PP1 at synapses and thus may play a role in regulation of substrates controlling synaptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (20) have noted distinct populations of dendritic spines in the primate cortex, containing either PP1␣ alone or both PP1␣ and PP1␥1. Interestingly, dopamine D1 receptors were only found in spines containing both PP1 isoforms, suggesting unique signaling properties of the PP1␣/PP1␥1-containing synapses.…”
Section: Figmentioning
confidence: 99%
“…PP1␥1 and PP1␣, but not PP1␤, were enriched in dendritic spines (6,8), where they associated with the actin-rich structure known as the post-synaptic density (PSD) (19). Recent studies (20) also suggested a heterogeneity of spines that contained either PP1␣ alone or both PP1␣ and PP1␥1. The neuronal actin-binding proteins, neurabin I and neurabin II/spinophilin, were also localized in PSD and bind PP1 (19,21,22).…”
mentioning
confidence: 99%
“…Heightened mesolimbic dopamine release following sexual experience (Kohlert and Meisel, 1999) is accompanied by enhanced postsynaptic coupling of dopamine D1 receptors to G-proteins (Bradley et al, 2004), resulting in activation of signaling pathways and nuclear transcription factors (Meisel and Mullins, 2006) mechanistically linked to long-term modifications of dendritic structure (Muly et al, 2001; Penzes et al, 2011; Penzes et al, 2001). As alterations to a select MSN phenotype could have significant impact on the overall functional output of the NAc (Albin et al, 1989; DeLong, 1990; Ikemoto, 2007; Sesack and Grace, 2010), an important but unstudied question centers on whether the persistent structural plasticity that occurs following sexual experience is cell-type specific.…”
Section: Introductionmentioning
confidence: 99%